الاقتصاد الأخضر والعمالة الخضراء، تقاطع المفاهيم والتحول في الاستراتيجيات - العربي, العربي; خوجة منصور, خالد (University of Eloued جامعة الوادي, 2021)
تروم هذه الدراسة؛ الإجابة على التحديات البيئية الناتجة عن النماذج التنموية المنتهجة التي عرفها العالم، وعجزها على تقديم حلول للعديد من الاكراهات، التي لم تكتفي برفاه الانسان، وإنما تجاوزت ذلك إلى مسألة الوجود. وبروز ظواهر خطيرة حتَّمت على الجميع التفكير فيها بجدية لمواجهتها، كالاحتباس الحراري والبطالة وغيرها. فجاء الاقتصاد الأخضر كمقاربة تنموية جديدة، تدعو إلى عقلنة استغلال الموارد الطبيعية، وتعزيز العمالة الخضراء. This study aims to; respond to the environmental challenges resulting from the development models known in the world, and its inability to provide solutions to the multiple limitations, which did not satisfy human well-being, but went beyond the issue of human life. The emergence of dangerous phenomena that forced everyone to think seriously to face them, such as global warming, unemployment, and other challenges. The green economy emerged as a new development approach, which called for rationalizing the exploitation of natural resources and promoting green employment.
مجلد12، عدد1
Keywords: الاقتصاد الأخضر، العمالة الخضراء، الصفقة الخضراء، النمو الذكي; Green Economy; Green Employment; Green Deal; Smart Growth.